Historicizing Islam: On the Agency of Siti Maryam in the Construction of Bima’s History of Islamization - Sila, Muhammad Adlin (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2018)
This article focuses on the understanding of Bima’s local interlocutors in the history of Islamization in the region, particularly in light of their construction of Bima vernacular manuscripts. This article provides the agency of Siti Maryam as the owner and caretaker of Samparaja museum who has given access to Bima’s manuscripts, locally called Bo’. Through in-depth interviews and participant observation, I examined how Siti Maryam as the manuscript’s owner constructs the entry of Islam to Bima, and how this understanding becomes the dominant storyline in explaining Bima’s history ranging from the pre-Islamic era to the period of Islamization. The aim of this article is not to discuss the truth or falsity in these historical accounts or to take sides. But all these varying historical accounts are important in providing a doorway into understanding the locally dynamic and religio-political practices of Islam in contemporary Bima.DOI: 10.15408/sdi.v25i1.5840